2015
DOI: 10.1364/oe.23.022553
|View full text |Cite
|
Sign up to set email alerts
|

Broadband polarization independent nanophotonic coupler for silicon waveguides with ultra-high efficiency

Abstract: Coupling of light to and from integrated optical circuits has been recognized as a major practical challenge since the early years of photonics. The coupling is particularly difficult for high index contrast waveguides such as silicon-on-insulator, since the cross-sectional area of silicon wire waveguides is more than two orders of magnitude smaller than that of a standard single-mode fiber. Here, we experimentally demonstrate unprecedented control over the light coupling between the optical fiber and silicon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 181 publications
(105 citation statements)
references
References 26 publications
0
104
0
Order By: Relevance
“…A 3-m-thick SiO 2 upper cladding layer was deposited using plasma-enhanced chemical vapor deposition. Broadband and efficient fiber-chip light coupling was achieved with subwavelength engineered mode transformers [3][4][5]. Since these mode transformers are narrow waveguides with a reduced modal confinement for optimum matching with the fiber mode, they are not substantially affected by jitter, as it will be discussed later in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3-m-thick SiO 2 upper cladding layer was deposited using plasma-enhanced chemical vapor deposition. Broadband and efficient fiber-chip light coupling was achieved with subwavelength engineered mode transformers [3][4][5]. Since these mode transformers are narrow waveguides with a reduced modal confinement for optimum matching with the fiber mode, they are not substantially affected by jitter, as it will be discussed later in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Since the first experimental demonstration of an optical waveguide with a subwavelength periodic core [4], these structures, also called subwavelength gratings (SWGs), have found many applications in integrated optics, for example as highly efficient fiber-chip couplers [3][4][5][6][7][8][9], low-loss waveguide crossings, evanescent field sensors [10,11], broadband directional couplers [12] and multimode interference (MMI) [13] couplers, polarization beam splitters [14][15][16], wavelength division [4] and mode division [17] multiplexers, delay lines [18], Fourier-transform spectrometers [19] and suspended (membrane) waveguides for mid-infrared applications [20]. Exhaustive reviews of SWG fundamentals and applications can be found in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Here we provide a short introduction on the general design of subwavelength waveguide devices (section 2), and then discuss two applications: suspended waveguides for the mid-infrared (section 3), and ultra-broadband couplers (section 4).…”
Section: Introductionmentioning
confidence: 99%
“…[3] However, at the junction between the interconnecting waveguide and the chip external coupling interface there is an intrinsic mode mismatch requiring mode conversion. [4][5][6][7][8][9][10][11][12] Tapers are used to gradually convert the mode area and the effective index of the guided mode, typically by varying the waveguide width. In Fig.…”
Section: Introductionmentioning
confidence: 99%